Towards the modeling of quantum-dot sensitized solar cells: from structural and vibrational features to electron injection through lattice-mismatched interfaces. Issue 34 (10th August 2016) - Szemjonov, Alexandra; Pauporté, Thierry; Ithurria, Sandrine; Pedetti, Silvia; Lequeux, Nicolas; Dubertret, Benoit; Ciofini, Ilaria; Labat, Frédéric
Abstract : Structure-property interplay investigation in quantum dot solar cells, using a combined experimental and theoretical approach. Abstract : A deep understanding of the structure–property interplay is essential for the design of complex devices such as quantum dot solar cells (QDSCs), in which interfacial recombinations are a major source of performance loss. This requires an accurate characterization of semiconductor interfaces both from the experimental and theoretical points of view, which remains problematic especially in the case of lattice-mismatched compounds. In this study, we combined theoretical and experimental methods to address this challenge. As an interesting alternative to spherical quantum dots (QDs), quasi two-dimensional CdSe nanoplatelets (NPLs) of different thicknesses have been linked to ZnO nanorods using the SH − functional group as a simple linker. These systems were characterized by Raman and UV-VIS spectroscopy. The experimental investigation suggested significant structural changes upon the interface formation. The latter was confirmed by a theoretical analysis using an accurate periodic density functional theory-based computational protocol, which enabled us to clarify the nature of these structural rearrangements. The vibrational and electronic properties of this system, as well as the electron injection efficiency from the NPL towards the ZnO surface have also been computed. The photogenerated charge transfer, in line with the working principle of QDSCs, turned out to be favored, but only partially. The mixed theoretical/experimental approach proposed here could be extended to other semiconductor heterostructures present in a wide variety of optoelectronic applications. In a broader perspective, it could contribute to better understand the working principle of these devices and enable the improvement of their performance.